Reducing labor pain with a birthing ball - Yetty Dwi Fara; Yona Desni Sagita (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Labor is a natural process. The genesis of pain influenced by the mother when facing labor can stimulate fear so that anxiety arises which ends in panic. For this reason, it is necessary to pay attention for to handling deal with pain in the first active phase of labor. One of the non-pharmacological methods of dealing with labor pain is birthing ball therapy. The research objective was to determine the effect of using a birthing ball on the effects of pain during the first active phase of labor. This type of research is a pre-experimental design with a one-group pretest-posttest design. The sample in this research were 18 mothers who labor. The results of the research obtained a p-value of 0.000 less than 0.05, which means that there is an effect of using a birthing ball toward the effects of labor pain in the first stage of labor active phase. Abstrak: Nyeri persalinan adalah hal yang normal dirasakan bagi setiap ibu bersalin. Nyeri yang dialami ibu saat persalinan berlangsung, dapat merangsang ketakutan ibu sehingga timbul kecemasan yang berakhir dengan kepanikan. Untuk itu diperlukan penanganan untuk mengatasi nyeri pada kala I persalinan. Salah satu metode non-farmakologi dalam mengatasi nyeri persalinan antara lain terapi birthing ball. Penelitian ini bertujuan untuk mengetahui apakah penggunaan birth ball dapat mengurangi nyeri persalinan pada kala 1 fase aktif. Jenis penelitian ini adalah penelitian kuantitatif dengan metode pra-eksperimen dengan rancangan one group pre test-post test group design. Sampel pada penelitian ini adalah 18 ibu bersalin. Hasil penelitian diperoleh p-value 0.000 less than 0.05 yang berarti terdapat pengaruh penggunaan birthing ball terhadap skala nyeri persalinan kala 1 fase aktif.